Making things international, - Salter, Mark B. (University of Minnesota Press, 2016)
"Drawing widely from contemporary social and critical thought, Making Things International 2 offers provocative interventions into debates about causality, connection, and politics through the notion of assemblage. Political assemblages, especially those that cross national borders, can be catalyzed by a host of surprising sparks. Present-day global systems are complex and interdependent, but the worn tools of traditional international relations theory are unsuited to the task of understanding how objects, ideas, and people come together to create, dispute, solve, or perhaps cause these political configurations. Contributors to this volume bring to their work a new sensitivity toward issues of power, authority, control, and sovereignty. The companion volume, Making Things International 1: Circuits and Motion, used things, stuff, and objects in motion to capture the material dynamics of global politics and to demonstrate the importance of the material. This volume builds on that conversation by examining objects that incite political assemblages. Specific subjects include fighter jets, smartphones, tents, HTTP cookies, representations of North Korea, and histories of the diplomatic cable, the orange prison jumpsuit, and container shipping. Contributors: Rune Saugmann Andersen, U of Helsinki; Josef Teboho Ansorge; Claudia Aradau, King's College London; Helen Arfvidsson; Alexander D. Barder, Florida International U; Tarak Barkawi, London School of Economics; Peter Chambers; Shine Choi, Seoul National U; Sagi Cohen; Thomas N. Cooke; Anna Feigenbaum, Bournemouth U; Andreas Folkers, Goethe-U Frankfurt; Fabian Frenzel, U of Leicester; Kyle Grayson, Newcastle U; Nicky Gregson, Durham U; David Grondin, U of Ottawa; Xavier Guillaume, U of Edinburgh; Emily Lindsay Jackson, Acadia U; Miguel de Larrinaga, U of Ottawa; Debbie Lisle, Queen's U Belfast; Mary Manjikian, Regent U; Nadine Marquardt, Goethe-U Frankfurt; Patrick McCurdy, U of Ottawa; Adam Sandor; Nisha Shah, U of Ottawa; Julian Stenmanns, Goethe-U Frankfurt; Casper Sylvest, U of Southern Denmark; Rens van Munster, Danish Institute for International Studies; Elspeth Van Veeren, U of Bristol; Srdjan Vucetic, U of Ottawa; Juha A. Vuori, U of Turku; Tobias Wille."--